Homogeneous photochemical water oxidation by biuret-modified Fe-TAML: evidence of Fe-V(O) intermediate - Panda, Chakadola; Debgupta, Joyashish; Diaz, David Diaz; Singh, Kundan K.; Gupta, Sayam Sen; Dhar, Basab B. (Journal of the American Chemical Society, 2014)
{Water splitting, leading to hydrogen and oxygen in a process that mimics natural photosynthesis, is extremely important for devising a sustainable solar energy conversion system. Development of earth-abundant, transition metal-based catalysts that mimic the oxygen-evolving complex of photosystem II, which is involved in oxidation of water to O-2 during natural photosynthesis, represents a major challenge. Further, understanding the exact mechanism, including elucidation of the role of active metal-oxo intermediates during water oxidation (WO), is critical to the development of more efficient catalysts. Herein, we report Fe-III complexes of biuret-modified tetra-amidomacrocyclic ligands (Fe-TAML; 1a and 1b) that catalyze fast, homogeneous, photochemical WO to give OD with moderate efficiency (maximum TON = 220

Vitro study of novel microparticle based silk fibroin scaffold with osteoblast-like cells for load-bearing osteo-regenerative applications - Parekh, Nimisha Anant; Hushye, Chandni; Warunkar, Saniya; Gupta, Sayam Sen; Nisal, Anuya (RSC Advances, 2017)
Silk Fibroin (SF) is today considered to be one of the most favorable materials for bone tissue engineering. We have prepared novel SF microparticle based 3D scaffolds, with appropriate pore size, pore interconnectivity and porosity, excellent mechanical properties and tunable bioresorption, while retaining the inherent biocompatibility of SF. These properties make them ideal candidates for osteoregenerative applications. Here, we report the in vitro cell viability, cell adhesion and proliferation with osetoblastic differentiation of MG 63 osteoblast-like cell line on these scaffolds. In addition, we have also modified the surface of these scaffolds using collagen type I and chitosan biopolymers. Our results show that although the SF scaffold does support in vitro cell attachment, proliferation and differentiation, this performance can be further enhanced using the surface coating approach. Also, the ALP activity and bone mineralization was found to be particularly superior in the chitosan modified scaffolds.

Trapping an elusive Fe(IV)-superoxo intermediate inside a self-assembled nanocage in water at room temperature - Gera, Rahul; De, Puja; Singh, Kundan K.; Jannuzzi, Sergio A. V.; Mohanty, Aisworika; Velasco, Lucia; Kumar, Pankaj; Marco, J. F.; Nagarajan, Kalaivanan; Pecharroman, Carlos; Rodriguez-Pascual, P. M.; DeBBeer, Serena; et al. (JOURNAL OF THE AMERICAN CHEMICAL SOCIETY, 2024)
Keywords: CATALYTIC EPOXIDATION; DIOXYGEN ACTIVATION; NONHEME IRON; X-RAY-ABSORPTION